Attributive Phrases in English-Language Abstracts of Engineering and Transportation Research - E. V. Rybakova (Научный диалог)
This study investigates the structural properties and thematic specificity of attributive phrases, including adjectives, in scientific abstracts related to the field of engineering and transportation. The objective is to explore the potential for representing pertinent themes through pre-modifying attributive phrases and to identify recurrent thematic components, alongside a list of adjectives that verbalize relevant characteristics. It is concluded that attributive phrases facilitate the verbalization of the following thematic components within the abstract: the high significance of the engineering and transportation field, the global demand for innovations in transportation, the implementation of environmentally friendly technologies, and the widespread use of modeling methodologies, including the creation of both real and virtual models. Frequent adjectives forming phrases with nouns denoting vehicles and transportation technologies have been identified, which represent various contemporary characteristics reflecting their modern properties. The compiled lists of attributive phrases, categorized by themes, can be utilized for training in the creation of abstracts for scientific articles in the engineering and transportation domain, as well as considered in the development of collocation dictionaries and thesauri.